2005
DOI: 10.1038/nsmb942
|View full text |Cite
|
Sign up to set email alerts
|

The Hsp70 Ssz1 modulates the function of the ribosome-associated J-protein Zuo1

Abstract: J-proteins are obligate partners of Hsp70s, forming a ubiquitous class of molecular chaperone machinery. The ribosome-associated Hsp70 of yeast Ssb binds nascent polypeptides as they exit the ribosome. Here we report that the ribosome-associated J-protein Zuo1 is the partner of Ssb. However, Zuo1 efficiently stimulates the ATPase activity of Ssb only when in complex with another Hsp70, Ssz1. Ssz1 binds ATP, but none of the 11 different amino acid substitutions in the ATP-binding cleft affected Ssz1 function in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
138
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(140 citation statements)
references
References 38 publications
2
138
0
Order By: Relevance
“…Hsp70L1 was able to functionally interact with zuotin. In this context it is important to recall that only the complex of zuotin and Ssz1p (RAC) is able to stimulate the ATPase of the yeast ribosome-bound Hsp70 Ssb1͞2p (6,8). As complementation by zuotin͞Hsp70L1 depended on an intact J domain of zuotin, Hsp70L1 most likely can replace Ssz1p and support zuotin's interaction with Ssb1͞2p (see Introduction).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hsp70L1 was able to functionally interact with zuotin. In this context it is important to recall that only the complex of zuotin and Ssz1p (RAC) is able to stimulate the ATPase of the yeast ribosome-bound Hsp70 Ssb1͞2p (6,8). As complementation by zuotin͞Hsp70L1 depended on an intact J domain of zuotin, Hsp70L1 most likely can replace Ssz1p and support zuotin's interaction with Ssb1͞2p (see Introduction).…”
Section: Discussionmentioning
confidence: 99%
“…4, lane 12). Finally, we used a nonfunctional J-domain mutant of zuotin (zuo1-H128Q), which is known to associate with ribosomes and Ssz1p but fails to functionally interact with Ssb1͞2p (6,8). Expression of Hsp70L1 in the presence of zuo1-H128Q failed to complement growth defects of ⌬zuo1⌬ssz1 (Fig.…”
Section: Mammalian Hsp70l1 Functionally Interacts With Yeast Zuotinmentioning
confidence: 99%
See 2 more Smart Citations
“…35,36 Neither the peptide binding domain nor the ATPase activity of Ssz1 is required for RAC function in vivo. 53,54 Thus, the importance of ribosome-association and Ssb stimulation for the anti-prionogenic function of the RAC can be assessed by deleting those 2 functional regions of Zuo1. Previous studies have shown that variants of Zuo1 with deletions of those regions are expressed at similar levels to wildtype Zuo1 but are not functional in vivo; specifically, deletion of the charged region eliminates the association of Zuo1 with ribosomes, whereas deletion of the J domain abolishes function without affecting ribosome association.…”
Section: Rac Suppression Of Prion Induction Requires Zuo1-dependent Amentioning
confidence: 99%